Study of the Density of States Distribution in the SiO2/Si Structure - Jurecka, Stanislav; Jamnicky, Igor (Communications - Scientific letters of the University of Zilina, 2010)
Interface properties of Al/SiO2 /Si MOS structures with NAOS oxide layer were analyzed by the construction of the capacitance-voltage model with the interface states. Energy distributions associated with the localized states in silicon band gap were modeled by the Gaussian distribution. Energy levels of localized states and the densities of interface states were determined. The results correspond with the results of the interface states study performed by the acoustic deep-level transient spectroscopy.